Historical Polar bases - preservation and management - Barr, Susan (red.); Chaplin, Paul (red.) (ICOMOS International Polar Heritage Committee, 2008)
Keywords: Antarktis; forskningsstasjoner; kulturminnevern; kulturvern; polarområdene

Norge i Antarktis : fra erobring til moderne forskning - Winther, Jan-Gunnar; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Tveraa, Torkild; Monsen, Oddbjørn (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norway in the Antarctic : from conquest to modern science - Winther, Jan-Gunnar; Tveraabak, Jacob; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Monsen, Oddbjørn; Goldman, Helle V (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Antarctic Treaty: Report of the Norwegian antarctic inspection under article VII of the Antarctic Treaty ([Justis- og beredskapsdepartementet], 2001)
Article VII of the Antarctic Treaty entitles each Consultative Party to designate observers who shall have the right to carry out unannounced on-spot inspections. The purpose of these inspections is to promote the objectives of and ensure compliance with the provisions of the Antarctic Treaty and the easures adopted under it. The observers shall be accorded complete freedom of access at any time to all areas of Antarctica, including all stations within those areas, as well as vessels and aircrafts at points of embarkation and disembarkation. Article 14 of the Protocol on Environmental Protection to the Antarctic Treaty commit the Consultative Parties to undertake inspections under Article VII of the Antarctic Treaty in order to promote the protection of the Antarctic environment and dependent and associated ecosystems, and to ensure compliance with the Environmental Protocol.
Keywords: Antarktis; Norge; forskningsstasjoner

Alvorlig uhell på Vostok-basen (Polarboken, 1984)
Keywords: Antarktis; forskningsstasjoner; logistikk

Snowdrifts around buildings and stores - Roots, Ernest Frederick; Swithinbank, Charles (Polar Record, 1955)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; akkumulasjon; forskningsstasjoner; snø

The white desert : the official account of the Norwegian-British-Swedish Antarctic Expedition - Giæver, John (Asahi Shimbun Sha, 1954)
Keywords: Dronning Maud Land; Maudheim (Antarktis); Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

The white desert : the official account of the Norwegian-British-Swedish Antarctic Expedition - Giæver, John (Chatto & Windus, 1954)
Keywords: Dronning Maud Land; Maudheim (Antarktis); ekspedisjoner; forskning; forskningsstasjoner; geografi; historie; oppdagelsesreiser; overvintring; sjøreiser

The Maudheim Expedition 1949-52 : part I - Schumacher, Nils Jörgen (Weather, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi

The Maudheim Expedition 1949-52 : part II - Schumacher, Nils Jörgen (Weather, 1952)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; forskningsstasjoner; meteorologi